2009
DOI: 10.1177/0310057x0903700215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin Deficiencies on Admission: Relationship to Hospital Mortality in Critically Ill Patients

Abstract: Optimal nutritional support, both in terms of route and formulation, in the critically ill remains controversial 1,2 . Apart from ensuring adequate caloric and protein intake, supplementation of micronutrients such as omega-3 fatty acids, glutamine, selenium and antioxidant vitamins has also been suggested to be important 3,4 . The rationale behind such practice is based on observational data in the critically ill.Oxidant stress is radically increased in critical illness and antioxidant capacity is consumed 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
(40 reference statements)
1
36
0
1
Order By: Relevance
“…In critical illness, the prevalence of thiamine deficiency is 10-20% upon admission (198,240) and can increase up to 71% during ICU stay, suggesting rapid depletion of this vitamin (198). Based on limited data, no association was detected between thiamine levels, markers of oxidative stress (198) and mortality (198,241). In one study, a significant negative correlation was reported between thiamine and lactic acid levels in patients with sepsis without liver dysfunction (240).…”
Section: Thiaminementioning
confidence: 99%
“…In critical illness, the prevalence of thiamine deficiency is 10-20% upon admission (198,240) and can increase up to 71% during ICU stay, suggesting rapid depletion of this vitamin (198). Based on limited data, no association was detected between thiamine levels, markers of oxidative stress (198) and mortality (198,241). In one study, a significant negative correlation was reported between thiamine and lactic acid levels in patients with sepsis without liver dysfunction (240).…”
Section: Thiaminementioning
confidence: 99%
“…Critical care patients require more vitamin B12 and folic acid, which may lead to relative vitamin B12 and folic acid deficiency and subsequently tothrombocytopenia, megaloblastic anemia, and hyperhomocysteinemia [84]. Studies have shown that vitamin B12 or folic acid deficiency is associated with the severity of patient condition [85]. Folic acid deficiency may also occur during RRT [86].…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Olivieri et al 14 conducted a study of 250 elderly patients with acute myocardial infarction admitted to a cardiac care unit (CCU) and found that vitamin B12 was not a significant predictor for cardiovascular-related mortality. Corcoran et al 15, 16 studied on the effect of vitamin B12 levels on mortality in the ICU and found that there was no association between B12 deficiency and mortality, and that weak correlations existed between B12 levels, CRP, and Sequential Organ Failure Assessment (SOFA) score, a measure of acuity in the ICU 17 . Manzanares and Hardy 18 conducted a review of studies on the relationship between B12 and mortality and noted that the data on B12 and mortality for critical care patients was scarce.…”
Section: Introductionmentioning
confidence: 99%